2008
DOI: 10.1177/0269881107083798
|View full text |Cite
|
Sign up to set email alerts
|

Review: Bupropion and SSRI-induced side effects

Abstract: Selective serotonin reuptake inhibitors (SSRIs) are a first line treatment option for millions of patients, due to the positive balance between efficacy and tolerability. However, some side effects associated with their use, can impair quality of life and compliance with treatment. This paper reviews the prevalence of sexual dysfunction, weight gain and emotional detachment during SSRI treatment, the profile of bupropion for each of these events and the ability of bupropion to reverse them. Double-blind trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 80 publications
3
48
1
2
Order By: Relevance
“…However in our study we found evidence for an association between mental disorders and weight gain independent of smoking, alcohol consumption, physical activity and social activity, which was in line with recent prospective studies that adjusted for lifestyle (Brumpton et al, 2013;Singh et al, 2014;Lasserre et al, 2014). The use of psychotropic medication has been suggested as a confounding factor in the association between psychopathology and weight change since medication use has shown to interact with mechanisms regulating food intake and appetite (Virk et al, 2004;Demyttenaere and Jaspers, 2008;Papakostas, 2008;Vieweg et al, 2008;Hasnain and Vieweg, 2013). Initially we found in a subsample of our study with persons having a current depressive and anxiety disorders that SSRI users as well as benzodiazepine users compared to non-users were more likely to gain weight.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However in our study we found evidence for an association between mental disorders and weight gain independent of smoking, alcohol consumption, physical activity and social activity, which was in line with recent prospective studies that adjusted for lifestyle (Brumpton et al, 2013;Singh et al, 2014;Lasserre et al, 2014). The use of psychotropic medication has been suggested as a confounding factor in the association between psychopathology and weight change since medication use has shown to interact with mechanisms regulating food intake and appetite (Virk et al, 2004;Demyttenaere and Jaspers, 2008;Papakostas, 2008;Vieweg et al, 2008;Hasnain and Vieweg, 2013). Initially we found in a subsample of our study with persons having a current depressive and anxiety disorders that SSRI users as well as benzodiazepine users compared to non-users were more likely to gain weight.…”
Section: Discussionsupporting
confidence: 91%
“…Some recent cross-sectional and longitudinal studies suggest that depressive and anxiety symptoms are associated with weight independently from lifestyle factors (physical activity, smoking and alcohol consumption) suggesting that there is no or a limited influence of lifestyle factors (Zhao et al, 2009). Furthermore the use of psychotropic medications, often prescribed for depressive and anxiety disorders, might be an additional explanatory risk factor for weight change (Virk et al, 2004;Demyttenaere and Jaspers, 2008;Vieweg et al, 2008;Hasnain and Vieweg, 2013). Underlying shared biological abnormalities such as inflammation, leptin or HPA-axis dysregulations could further play a linking role between mental health and weight change (Bjorntorp, 2001;Bornstein et al, 2006;Pasco et al, 2008;Vreeburg et al, 2009;Milaneschi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…All other antidepressants were significantly more likely than placebo to be associated with "sexual dysfunction" (as a unitary category), and nearly all were significantly more likely than placebo to be associated with dysfunction in each phase of the sexual response 67 . Bupropion appears associated with a significantly lower rate of treatment-emergent sexual dysfunction than the SSRIs escitalopram, fluoxetine, paroxetine or sertraWorld Psychiatry 17:1 -February 2018 line 68 , which may reflect the predominantly noradrenergicdopaminergic mechanism of action of that drug 69 .…”
Section: Influence Of Treatment Of Depression On Sexualitymentioning
confidence: 99%
“…Treatment with SSRIs has also been associated with emotional detachment, although controversy still exists on this issue [287]. SSRIs may have slightly more side effects than bupropion, including sexual dysfunction and weight gain [287].…”
Section: Relative Safetymentioning
confidence: 99%